Are Saturn's Interchange Injections Organized by Rotational Longitude?. Issue 3 (28th March 2019) - Azari, A. R.; Jia, X.; Liemohn, M. W.; Hospodarsky, G. B.; Provan, G.; Ye, S.‐Y.; Cowley, S. W. H.; Paranicas, C.; Sergis, N.; Rymer, A. M.; Thomsen, M. F.; Mitchell, D. G.
Abstract: Saturn's magnetosphere has been extensively studied over the past 13 years with the now retired Cassini mission. Periodic modulations in a variety of magnetospheric phenomena have been observed at periods close to those associated with the emission intensity of Saturn kilometric radiation (SKR). Resulting from Rayleigh‐Taylor like plasma instabilities, interchange is believed to be the main plasma transport process in Saturn's inner to middle magnetosphere. Here we examine the organization of equatorially observed interchange events identified based on high‐energy (3–22 keV) H + intensifications by several longitude systems that have been derived from different types of measurements. The main question of interest here is as follows: Do interchange injections undergo periodicities similar to the Saturn kilometric radiation or other magnetospheric phenomena? We find that interchange shows enhanced occurrence rates in the northern longitude systems between 30° and 120°, particularly between 7 and 9 Saturn Radii. However, this modulation is small compared to the organization by local time. Additionally, this organization is weak and inconsistent with previous findings based on data with a limited time span. Plain Language Summary: When estimating the rotation rate of Jupiter and Saturn, scientists often use a periodic signal of radio emission from the planet's auroral region. At Saturn this emission is called the Saturn kilometric radiation (SKR), and unlike Jupiter, the period of SKR is observed to vary over time. Similar periodic variations have also been observed in particle energy and magnetic fields, suggesting that this periodicity is a fundamental property of the Saturn space environment. In this work, we ask if these same repetitions can be seen in a process called interchange injection. To do this, we analyze interchange's occurrence rate, as observed in particle data from the Cassini spacecraft, with respect to two longitude systems previously derived from the observed periods of the SKR emission. We find that interchange occurrence shows only weak organization in these longitude systems as compared to organization by local time. Key Points: Interchange injections, identified from an automated detection method, shows strongest organization in local time compared to longitude Longitude system dependence of equatorial interchange injections exists, but it is weak and inconsistent to previous works Interchange occurrence rates weakly peak at 90° in northern SLS‐5 and PPO between 7 and 9 Saturn Radii but occur at all longitudes and seasons